2018
DOI: 10.1073/pnas.1810823115
|View full text |Cite
|
Sign up to set email alerts
|

A single phosphorylation site of SIK3 regulates daily sleep amounts and sleep need in mice

Abstract: Sleep is an evolutionally conserved behavior from vertebrates to invertebrates. The molecular mechanisms that determine daily sleep amounts and the neuronal substrates for homeostatic sleep need remain unknown. Through a large-scale forward genetic screen of sleep behaviors in mice, we previously demonstrated that the Sleepy mutant allele of the Sik3 protein kinase gene markedly increases daily nonrapid-eye movement sleep (NREMS) amounts and sleep need. The Sleepy mutation deletes the in-frame exon 13 encoding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
79
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 62 publications
(85 citation statements)
references
References 33 publications
5
79
1
Order By: Relevance
“…We were able to test this prediction by studying the function of a KIN-29 protein with a conserved Serine 517 mutated to Alanine ( S9A Fig ). The motivation for making this particular mutant was the observation that a homologous change in the mouse SIK3 gene results in a sleepy phenotype [78]. While we did not observe a sleepy phenotype in the kin-29(S517A) mutants, we found that KIN-29(S517A) mutant protein did not move to the nucleus during lethargus ( Fig 7A-B ); moreover, it did not rescue the sleeping-defective of kin-29 null mutants ( Fig 7C ).…”
Section: Resultsmentioning
confidence: 99%
“…We were able to test this prediction by studying the function of a KIN-29 protein with a conserved Serine 517 mutated to Alanine ( S9A Fig ). The motivation for making this particular mutant was the observation that a homologous change in the mouse SIK3 gene results in a sleepy phenotype [78]. While we did not observe a sleepy phenotype in the kin-29(S517A) mutants, we found that KIN-29(S517A) mutant protein did not move to the nucleus during lethargus ( Fig 7A-B ); moreover, it did not rescue the sleeping-defective of kin-29 null mutants ( Fig 7C ).…”
Section: Resultsmentioning
confidence: 99%
“…An alternative possibility is that sleep propensity may be enhanced if some of the strong wake-promoting areas are inhibited, consistent with the idea that sleep represents a default state of a neural network or the whole organism (Bandarabadi et al, 2020;Krueger et al, 2013). Therefore, even if accumulation of sleep need, in some form, occurs across many distributed brain networks (Bridi et al, 2019;Bruning et al, 2019;Honda et al, 2018;Lazarus et al, 2019;Muheim et al, 2019;Noya et al, 2019;Shi and Ueda, 2018;Tatsuki et al, 2016;Williams and Naidoo, 2020), it is likely that state switching is initiated from a relatively limited set of brain circuits, which have the capacity to integrate sleep-wake history related signals with other ecological and homeostatic demands. Whilst the biological substrate of global sleep homeostasis remains unclear, the question of which brain areas are involved in encoding the time spent awake or asleep seems tractable.…”
Section: Discussionmentioning
confidence: 69%
“…3F) or aspartic acid (S551D), mice showed a decreased NREM sleep time similar to Sleepy mutant mice. 228) SIK3 protein variants exhibited decreased binding to 14-3-3 proteins compared with the wild-type SIK3 protein. 228) Although it is unclear whether binding to 14-3-3 protein itself is important for sleep control, changes in the biochemical properties of the SIK3 protein may lead to a reduced waking time.…”
Section: Reverse Genetic Studies On Sleep In Micementioning
confidence: 91%